Indirect evolution versus strategic delegation: A comparison of two approaches to explaining economic institutions - Martin Dufwenberg; Werner Güth (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1997)
The two major methods of explaining economic institutions, namely by strategic choices or by (indirect) evolution, are compared for the case of a homogenous quadratic duopoly market. Sellers either can provide incentives for their agents to care for sales (amounts) or evolve as sellers who care for sales in addition to profits. Whereas strategic delegation does not change the market results as compared to the usual duopoly solution, indirect evolution causes a more competitive behavior. Thus the case at hand suffices to demonstrate the difference between the two approaches in explaining economic institutions.
urn:nbn:de:kobv:11-10064149
Keywords: 330